Characterisation of the T cell response during Staphylococcus aureus nasal colonisation - Daly, Clíodhna (Trinity College Dublin. School of Biochemistry & Immunology. Discipline of Biochemistry, 2025)
While Staphylococcus aureus is primarily recognised as an invasive pathogen, it is also an important component of the normal human microbiome, persistently colonising the nasal tissue (NT) of a significant proportion of the population. The impact that S. aureus asymptomatic colonisation has on the host immune system is incompletely understood. S. aureus memory responses at colonised barrier sites could impact vaccine responsiveness in a pre-exposed population, thus a detailed understanding of the immunological imprint left by colonising S. aureus is crucial for effective vaccine design. This thesis aimed to provide a comprehensive characterisation of long-lasting memory T cells responses within the NT during S. aureus nasal colonisation and the potential impact that these memory cells have for the host. Using both conventional and germ-free (GF) mouse models of S. aureus nasal colonisation it was determined that CD4+ tissue resident memory (TRM) T cells are expanded in the NT in response to S. aureus colonisation and remained poised for rapid reactivation upon secondary S. aureus exposure. Intriguingly, these cells were also capable of non-specific reactivation during LPS and Klebsiella pneumoniae stimulation, with IL-17+ CD4+ TRM cells in S. aureus colonised mice enhancing protection against K. pneumoniae. Ex vivo antigen recall assays established that S. aureus specific CD4+ TRM cells undergo bystander activation, responding to pro-inflammatory cytokines in the absence of antigen stimulation. IL-17+ γδ+ TRM cells were similarly expanded in the NT during S. aureus colonisation and could also undergo reactivation upon subsequent exposure to S. aureus and non-specific stimuli. γδ+ TRM cells in the S. aureus colonised NT were specifically determined to be Vγ6+ and required the presence of a complete microbiome to be retained in the NT. Finally, the project demonstrated that S. aureus nasal colonisation is associated with an expansion of TIGIT+ Treg cells within the NT which function to promote S. aureus persistence at this site, but which could also potentially impede vaccine induced antigen specific recall responses. Overall, this project demonstrates that S. aureus nasal colonisation shapes long-lasting memory T cell responses, with significant consequences for immune responses during subsequent bacterial exposure and potentially impacting vaccination responses in colonised individuals.
APPROVED